2009
DOI: 10.1590/s0102-311x2009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à duração do aleitamento materno em crianças de famílias de baixa renda da região sul da cidade de Curitiba, Paraná, Brasil

Abstract: Fatores associados à duração do aleitamento materno em crianças de famílias de baixa renda da região sul da cidade de Curitiba, Paraná, BrasilFactors associated with duration of breastfeeding for children of low-income families from southern Curitiba, Paraná State, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
23

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
(25 reference statements)
1
12
2
23
Order By: Relevance
“…At 6 months of age, the cumulative probability of breastfeeding was 54.9%, the approximate value of the prevalence found in a 2012 study conducted in the state of Rio Grande do Sul (56.4%) 7 . Contrasted to the results of the present study, a 2009 study performed in Curitiba with children from low-income families showed that 54.2% of children up to 2 years of age were still being breastfed 15 . The differences observed in the duration and prevalence of breastfeeding among populations with geographic proximity, as is the case of Curitiba and Almirante Tamandaré, highlights the complex network of variables capable of influencing this practice and justifies the development of studies to identify the factors associated with weaning in specific communities.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At 6 months of age, the cumulative probability of breastfeeding was 54.9%, the approximate value of the prevalence found in a 2012 study conducted in the state of Rio Grande do Sul (56.4%) 7 . Contrasted to the results of the present study, a 2009 study performed in Curitiba with children from low-income families showed that 54.2% of children up to 2 years of age were still being breastfed 15 . The differences observed in the duration and prevalence of breastfeeding among populations with geographic proximity, as is the case of Curitiba and Almirante Tamandaré, highlights the complex network of variables capable of influencing this practice and justifies the development of studies to identify the factors associated with weaning in specific communities.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study with children from the south of Brazil belonging to low income families also identified low birth weight as a risk factor in weaning before two years of life 15 . Low birth weight, primarily when associated with prematurity, may cause alterations in the suction of the baby during breastfeeding, consequently resulting in precocious weaning 17 .…”
Section: Discussionmentioning
confidence: 96%
“…Sendo assim, o incentivo ao aleitamento materno no pré-natal é uma ação de baixa complexidade, constituindo-se em importante aliada na promoção da saúde e nutrição materno-infantil 30,34,35 .…”
Section: Resultsunclassified
“…Rooming-In (RI) 24 hours per day was associated with less probability of interrupting breastfeeding when compared with women who did not stay with their babies in the same system (21) . In another study, RI in the nursing home was a factor for the protection of exclusive breastfeeding (22) . With regard to women's opinion about this practice, the study revealed that 96% of the mothers approved of this system and 66% alleged that RI favored breastfeeding (23) .…”
Section: Step 7 -Practice Rooming-in -That Is Allow Mothers and Infamentioning
confidence: 96%